(untitled) (Global Journal of Management and Business Research, 2017)
Bangladesh is a beautiful country with a lot of scenic tourist attractions in different locations around the country. As the global demand for tourism is increasing the situation here in Bangladesh is not different. Different locations of Bangladesh can be attractive both for the domestic and international tourists. The contribution of the same industry to the world economy is considerable. Many countries are now depending on this sector for earnings foreign currency as direct way of economic growth. All the destinations of the country is trying to achieve more gain by developing this industry. To develop this industry as a whole, a vital consideration normally goes to the improvement Hotels and Resorts conditions of the country. If the tourists do not feel safe and comfortable about the place where they visit, then the chances of losing these tourists appear higher. Hotels and resorts are trying to attract more tourists by adopting appropriate marketing techniques and strategies.